2021
DOI: 10.1007/s11423-021-09963-w
|View full text |Cite
|
Sign up to set email alerts
|

Supporting interdisciplinary collaborative concept mapping with individual preparation phase

Abstract: Concept mapping facilitates the externalisation and internalisation of knowledge by individuals during collaborative knowledge construction. However, not much is known about the individual and collaborative learning processes during collaborative concept mapping (CCM) in interdisciplinary knowledge construction. Premised on literature on collaboration scripts to scaffold the collaboration process, this study investigates the effect of an individual preparation phase prior to collaborative work on the epistemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 39 publications
0
3
0
5
Order By: Relevance
“…Heterogeneous groups tended to reach consensus and make decisions by integrating both sides' opinions when there was an individual preparation, compared to more quick-consensus building practices in the immediate collaboration condition. These behaviours all indicated the higher-order thinking process when students were more "prepared" for the teamwork (Mende et al, 2021), which also corresponds to the higher quality of their design solutions as the collaboration product (Farrokhnia et al, 2019;Tan et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Heterogeneous groups tended to reach consensus and make decisions by integrating both sides' opinions when there was an individual preparation, compared to more quick-consensus building practices in the immediate collaboration condition. These behaviours all indicated the higher-order thinking process when students were more "prepared" for the teamwork (Mende et al, 2021), which also corresponds to the higher quality of their design solutions as the collaboration product (Farrokhnia et al, 2019;Tan et al, 2021).…”
Section: Conclusion and Discussionmentioning
confidence: 92%
“…The main role of individual preparation before collaboration, compared with direct collaboration, lies in several aspects: activating prior knowledge, exposing knowledge gaps, facilitating engagement, and increasing sensitivity to noticing (Lam & Kapur, 2018). The individual preparation before collaboration, recognised in previous empirical studies (e.g., Beers et al, 2006;Farrokhnia et al, 2019), showed higher learning gains (Salomon, 1997;Stahl, 2006), higher motivation for group work (Van Boxtel et al, 2000), better collaboration products (Engelmann et al, 2014;Engelmann et al, 2009) as well as more indepth knowledge co-construction discourse (Tan et al, 2021). Meanwhile, a series of studies by Tsovaltzi et al (2015) identified knowledge solidification as a result of individual preparation before collaboration, and that students became less likely to accept alternative opinions during the following discussion, which directly interrupted the knowledge co-construction at the group level.…”
Section: Literature Review Individual Preparation Before Collaborationmentioning
confidence: 95%
“…Asimismo, los conocimientos previos del estudiante reducen la carga intrínseca y mejoran la eficiencia del aprendizaje colaborativo, como muestra un experimento donde una preparación individual previa facilita la asimilación de conocimientos durante la colaboración grupal posterior (Tan, De Weerd y Stoyanov, 2021); así como otro estudio que revela que la experiencia en tareas relevantes optimiza la coordinación grupal por la menor carga extrínseca (Zambrano et al, 2019), de modo que el nivel de participación, motivación y saberes existentes impactan en la distribución de la carga cognitiva pertinente en actividades colaborativas.…”
Section: Recursos Cognitivos Y Aprendizaje Colaborativounclassified
“…Independientemente de la teoría particular en la cual se apoyen, los autores, desde el socioconstructivismo, coinciden en hacer especial hincapié en las interacciones sociales. Es justamente en estas interacciones y en la negociación que los estudiantes logran construir nuevos conocimientos y generar significados compartidos (Borge et al, 2018;Heimbuch et al, 2018;Rojas et al, 2019;Hayashi, 2020;Heinonen et al, 2020;Pham, 2021;Tan et al, 2021).…”
Section: Orientación Teóricaunclassified
“…Otro ejemplo donde se analizó el discurso colaborativo es el artículo de Tan et al (2021). La diferencia de este artículo en relación a los anteriores radica en el hecho de que, en este, los estudiantes en grupos de cinco y seis integrantes construyeron un mapa conceptual colaborativo en una modalidad de enseñanza presencial.…”
Section: Tabla 2 Variables Y Modalidades De Las Publicaciones Más Par...unclassified